PENGARUH NAUNGAN DAN PUPUK KALIUM TERHADAP PERTUMBUHAN TANAMAN NILAM (Pogostemon cablin Benth.) - Sisgianto Sisgianto; Nurbaiti Nurbaiti; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aimed to see the effect of shade and potassium fertilizer on the growth of patchouli plants, to get the best potassium potassium condensation on each level of shade provided and to get a better shade level at each dose of potassium fertilizer provided. The experiment was conducted in experimental station of Agriculture Faculty of Universitas Riau from December 2015 to April 2016. This research is a split plot design with shade as main plot and potassium fertilizer as plot child. The main plot consisted of 3 treatment levels: N0 (No shade), N1 (Shade 50%), N2 (Shade 75%) and sub plot consisted of 4 treatment levels: K0 (Without KCl fertilizer), K1 (Fertilizer KCl 0.125 g perpolybag or 50 kg.ha-1), K2 (KCl fertilizer 0.250 g per polybag or 100 kg.ha-1), K3 (KCl fertilizer 0.375 g per polybagor 150 kg.ha-1). Data has been analyzed with variance and tested further with Duncan test at 5% level. The result of this research showed that of shade 75% gave better growth of patchouli plants. Giving doses of KCl 0.375 g per polybag resulted in better growth of patchouli plants. Giving 75% of the various doses of KCl fertilizer provided gives better result on observation of branch length, number of primary branches, root volume and dray weight of the plant. Giving dosage of KCl 0.375 g per polybag at various shade levels gave better result on observation of branch lenght, number of primary branch, root volume and dry weight of plant. Keywords: Shade, Potassium Fertilizer and Patchouli Plant